Population-based study of the association between asthma and exogenous female sex hormone use - Jimi Choi; Won Jai Jung; Sang Yeub Lee; Sue In Choi; Byung-Keun Kim; Eun Joo Lee (BMJ Open)
Objectives Several studies have suggested the influence of exogenous hormones on asthma, but the results are still conflicting. Moreover, there has been little associated research on Asian population. This study aimed to assess the association between use of exogenous female sex hormones and asthma in Korean women.Design Korea National Health and Nutrition Examination Survey (KNHANES) is a nationwide programme to assess national health and nutritional status in Korea. A population-based study was conducted to analyse the relationship between self-reported asthma and exogenous hormones using the KNHANES between 2007 and 2012.Participants The study sample included 6874 premenopausal and 4912 postmenopausal women aged 30–65.Outcome measures KNHANES data comprised health interviews and physical examinations. Questionnaires regarding asthma, reproductive factors and exogenous hormones were included.Results Among postmenopausal women, 3.4% reported doctor-diagnosed asthma. Hormone replacement therapy (HRT) was associated with increased odds of doctor-diagnosed asthma (OR 1.56; 95% CI 1.04 to 2.35), while the association between HRT and wheeze in the last 1 year was not significant (OR 1.37; 95% CI 0.95 to 1.96). In premenopausal women, the prevalence of asthma was 2.3%. Use of oral contraceptives (OCs) was associated with an increased odds of doctor-diagnosed asthma (OR 1.67; 95% CI 1.01 to 2.76) and wheeze in the last 1 year (OR 1.88; 95% CI 1.31 to 2.69). These associations were dominant among non-obese women (body mass index <25 kg/m2; OR 2.36; 95% CI 1.34 to 4.17 for asthma and OR 2.15; 95% CI 1.43 to 3.23 for wheeze).Conclusions HRT and OCs were associated with increased asthma in postmenopausal and premenopausal women, respectively. The association between OC use and asthma was strong in non-obese premenopausal women.